Cuidado y autocuidado en familias con un miembro con diagnóstico de trastorno afectivo bipolar (TAB), pertenecientes al Grupo Psicoeducativo del Departamento de Psiquiatría de la Universidad de Antioquia (2013)
ABSTRACT: Objective: To analyze the families from the Psychoeducational Group of the Psychiatry Department of the University of Antioquia that have one member with bipolar disorder (BD) in order to identify their care-related practices. Method: A comprehensive research project using the phenomenological and hermeneutic method. Semi-structured interviews were conducted with twelve families. The data obtained were analyzed using the Atlas ti qualitative software. Results: Two main categories emerged: 1. Care and family life course and 2. Care and self-care in relation to bipolar disorder. The first category manifests itself through practices such as: Taking care of the diseased person by being physically present, providing physical or emotional support, or by transferring care-related actions to other family members. Two main perspectives could be identified in the second category, namely: the caretaker’s perspective and that of the person being taken care of. Two tendencies were found regarding the first one: taking care of others brings about transformations in the caretakers and taking care of others is tough. The second perspective has the same number of tendencies: self-care as poetics and taking care of oneself in order to go from the Diving Bell to the Butterfly. Conclusions: Taking care of others is a way of building humanity. Conducting research on care and self-care practices (i.e. the practices of both the caretaker and the person being taken care of) results in a more aesthetic way of providing care and a more aesthetic patientcaretaker dyad.